2002
DOI: 10.1523/jneurosci.22-19-08438.2002
|View full text |Cite
|
Sign up to set email alerts
|

Structure/Function Analysis of Ca2+Binding to the C2A Domain of Synaptotagmin 1

Abstract: Synaptotagmin 1, a Ca2+ sensor for fast synaptic vesicle exocytosis, contains two C2 domains that form Ca2+-dependent complexes with phospholipids. To examine the functional importance of Ca2+ binding to the C2A domain of synaptotagmin 1, we studied two C2A domain mutations, D232N and D238N, using recombinant proteins and knock-in mice. Both mutations severely decreased intrinsic Ca2+ binding and Ca2+-dependent phospholipid binding by the isolated C2A domain. Both mutations, however, did not alter the apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 34 publications
(57 reference statements)
8
119
0
Order By: Relevance
“…Similar function has been attributed to Ca1 in the case of synaptotagmin I (C2A domain) (29,30). In contrast, Ca1 seems not to be essential for the membrane binding of cytosolic phospholipase A 2 (31).…”
Section: Role Of Ca 2ϩ Ions In the C2 Domain-dependent Translocation supporting
confidence: 54%
“…Similar function has been attributed to Ca1 in the case of synaptotagmin I (C2A domain) (29,30). In contrast, Ca1 seems not to be essential for the membrane binding of cytosolic phospholipase A 2 (31).…”
Section: Role Of Ca 2ϩ Ions In the C2 Domain-dependent Translocation supporting
confidence: 54%
“…For the hippocampal neuronal cultures, offspring from D232N/D238N-mutant compound heterozygotes were used. All genotyping was performed as described previously (Fernandez-Chacon et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a major question is now whether synaptotagmin-1 acts primarily as a Ca 2ϩ -dependent phospholipid binding protein in triggering exocytosis, with its SNARE binding having a separate role (possibly in priming vesicles for subsequent release), or whether the interactions of synaptotagmin-1 with both SNAREs and phospholipids collaborate in Ca 2ϩ triggering of neurotransmitter release. We previously analyzed two aspartate-to-asparagine substitutions in the Ca 2ϩ -binding site of the C 2 A domain (D232N and D238N) that interfere with Ca 2ϩ binding to the C 2 A domain in slightly different ways, but do not alter its atomic structure, and have little effect on Ca 2ϩ -dependent phospholipid binding by synaptotagmin-1 (Fernandez-Chacon et al, 2002). In knock-in mice, the D238N mutation produced no major change in synaptic function, but the D232N mutation caused an unexplained increase of synaptic depression during repetitive stimulation (Fernandez-Chacon et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected from structural and functional data, the D405A point mutation should disrupt the most important residue in a putative Ca 2q /phospholipid nucleation site of the 'C2-like' domain III (Strobl et al, 2000;Alexa et al, 2004). A number of site-directed mutagenesis studies with the C2 domains of PKCa (Bolsover et al, 2003), cPLA (Bittova et al, 1999), synaptotagmin (Fernandez-Chacon et al, 2002) and other C2 domain proteins have shown that neutralising mutations of the acidic residues in the Ca 2q -binding loops of C2 domains usually result in an important loss of affinity for membrane lipids. Our data suggest that the contribution of the single acidic-loop residue mutated here is minimal in the context of a heterodimeric calpain.…”
Section: Lipid-binding Sites Of M-calpain: Roles Of Domain V and The mentioning
confidence: 99%